Territories and objects of natural reserve fund as parts of Ichnianskyi National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Ichnianskyi National Nature Park was created in 2004. It includes 10 protected areas of other categories: Dendrological park of national importance "Trostianets" hydrological reserves "Kniazky" and "Dovhyi Yar", landscape reserves "Urochyshche Kuty" and "Volyk", forest reserves "Kuty" "Sofiivka-Romanivshchyna" and "Dovhyi Yar", natural reserve "Sofiivka", botanical monument of nature of local importance "Bahatovikovyi Dub". Information on vegetation of all these areas is provided. It was found that forest and landscape reserves have similar coenotic and floristic composition but different degrees of preservation. Based on the study results, it is recommended to reorganize the objects in connection with their inclusion in the Ichnianskyi National Nature Park, the conservation status of which is higher, as well as make changes to the zoning. More valuable areas (sq. 23–26, 37, 43, 46–52, 57–60, 75–77 of Zhadkivske forestry) are recommended for inclusion in the protected zone, and less valuable (sq. 35, 36, 41, 42 of Zhadkivske forestry) – in the zone of the regulated recreation, limiting the access of visitors. This will help to ensure adequate protection of indigenous natural compexes of Ichnianskyi National Nature Park.
Keywords: Ichnianskyi National Nature Park, protected area, zoning.